EXERCISE REVERSES AGE-ASSOCIATED MORPHOMETRIC CHANGES IN THE RAT HEART (Fiep Bulletin - online, 2015)
Aging of the heart is associated with a reduction in the number of myocites, a lower capillary density and accumulation of collagen within the myocardium. The aim of this investigation was to determine if these changes in the heart can be reversed by moderate aerobic-exercise. Fifteen Wistar rats were studied: 5 rats aged 6 months (initial group) and 10 other rats aging 12 months, 5 of which were sedentary and 5, runner rats (60 min/day, 5 days/week at 30 m/min on a tredmill). Several ultrathin sections obtained from the left ventricle were examined in the electron microscope and electronmicrographs were used for morphometric studies of the myocardium.  The density of myocites and capillaries and the transverse cross-sectional area of myocites decreased in the sedentary rats, whereas in the trained rats, they remained unchanged. The interstitial tissue also increased in hearts of sedentary rats but not in the trained rats. The cross-sectional areas of capillaries increased significantly in the sedentary rats, possibly as a compensatory mechanism, due to the loss of capillaries with aging. These findings provide evidence of the effect of a moderate intensity exercise upon aging of cardiac myocites and capillaries. It could be postulated that this is a positive change since myocites and capillaries becomes more like that of younger rats.
Keywords: Myocardial aging; exercise; morphometry